A preparation method and application of manganese oxide composite coating electrode

By using Yb-doped MnO2 protective layer and Ce-doped Mn2O3 catalytic layer in metal-based MnO2 electrodes, the problems of short electrode life and low electrocatalytic activity are solved, and the electrode service life is significantly extended and the catalytic activity is improved.

CN114561642BActive Publication Date: 2025-05-02湖南株冶有色金属有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210183036.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-27
Publication Date
2025-05-02
Estimated Expiration
2042-02-27

AI Technical Summary

Technical Problem

The existing metal-based MnO2 electrode has a short life and low electrocatalytic activity, resulting in limited application in non-ferrous metal metallurgy.

Method used

The Yb doped MnO2 layer was prepared by electrodes using a manganese oxide composite coating electrode, including a metal substrate, an oxidation-resistant intermediate layer, a Yb doped MnO2 protective layer and a Ce doped Mn2O3 catalytic layer, and a Ce doped Mn2O3 catalytic layer was prepared by thermal decomposition method to enhance the binding force and catalytic activity of the electrode.

Benefits of technology

It significantly extends the service life of the electrode, at least 6 times longer, reduces the anode potential, and improves the durability and catalytic activity of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114561642B_ABST
    Figure CN114561642B_ABST
Patent Text Reader

Abstract

The present invention discloses a manganese oxide composite coating electrode and a preparation method thereof. The composite coating electrode includes a metal substrate, an antioxidant intermediate layer, a Yb doped MnO2 protective layer, and a Ce doped Mn2O3 catalytic layer. The metal substrate is selected from at least one of Al, Ti, Fe, or their alloys, and the antioxidant intermediate layer is selected from at least one of TiN, TiB2, TiC, and WC. The manganese oxide composite coating electrode is prepared in sequence by pretreating the metal substrate, preparing the antioxidant intermediate layer, preparing the Yb doped MnO2 layer, and preparing the Ce doped Mn2O3 layer. The present invention combines the advantages of two manganese oxide layers, further improves the service life of the electrode, enhances the overall performance of the traditional metal-based MnO2 coating electrode, and has a lower cost compared with the metal-based noble metal oxide electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrodes in hydrometallurgy, and in particular relates to a preparation method and application of a manganese oxide composite coating electrode. Background Art

[0002] In the process of non-ferrous metal metallurgy, taking the electrodeposition of metallic zinc as an example, during the electrolysis process, the cathode potential, solution voltage drop, contact voltage drop, and anode potential account for 24%, 15%, 1%, and 60% of the cell voltage respectively, and nearly half of the anode potential is caused by the oxygen evolution overpotential. The most widely used anode at present is the Pb-Ag alloy anode, which has the following problems that need to be solved:

[0003] (1) The electrocatalytic activity of Pb alloy anode for oxygen evolution is poor. Taking zinc electrolysis as an example, the overpotential of oxygen evolution during the electrolysis process is about 0.8V, which causes a large amount of useless power consumption and causes serious waste.

[0004] (2) Pb alloy has poor corrosion resistance (large anode loss, short life, corrosion products contaminate cathode products). The PbO2 protective film generated on the surface of the Pb alloy anode during the polarization process is loose and porous, and is easily detached under the erosion of oxygen and liquid flow. On the one hand, the Pb alloy substrate needs to be continuously oxidized for self-repair, causing corrosion of the anode. On the other hand, the corrosion products will enter the electrolyte and enter the cathode through inclusion or discharge, contaminating the cathode product.

[0005] (3) The density of Pb alloy anode is as high as 11.34g / cm 3 , low strength (prone to creep, resulting in short circuit between the anode and cathode, reducing cathode current efficiency, even anode damage, and increasing labor intensity).

[0006] (4) Precious metal Ag needs to be added during the preparation of Pb alloy anodes, which greatly increases the cost of the anode.

[0007] (5) Mn 2+ Severe depletion. Due to the continuous oxidation of manganese ions, a large amount of anode mud is generated in the electrolyte, which makes it very difficult to clean the electrolytic cell. In addition, the highly active powdered MnO2 produced is mixed with metallic lead, and the lead removal process is complicated, making it difficult to use MnO2.

[0008] In order to improve the above shortcomings, the preparation and improvement of titanium-based DSA anodes have attracted much attention in recent years. The inventors found through preliminary experiments that DSA anodes with γ-MnO2 or Mn2O3 as the catalytic layer can inhibit the Mn in the electrolyte. 2+The depletion of MnO2 greatly reduces the amount of anode mud generated, and it is an ideal catalyst to replace RuO2, IrO2, PbO2 and other oxide catalyst layers. However, the current MnO2 electrodes are all prepared with a single MnO2 layer as the catalyst layer. The short service life has greatly limited its application in non-ferrous metal metallurgy, and also restricted the further development of DSA anodes. In addition, the middle layer of the electrode is mostly made of oxides such as tin and antimony. The preparation temperature of the oxide layer of tin and antimony is as high as 400°C, which is very easy to cause oxidation of the substrate, and its service life can only reach about half a year. Although many scholars have improved the performance of metal-based MnO2 electrodes by doping and other methods, the service life and oxygen evolution activity are almost biased, or the improvement is not obvious. Although precious metal oxides such as RuO2 and IrO2 have extremely high oxygen evolution activity and long service life, their high prices seriously limit their application in electrochemical metallurgy.

[0009] Therefore, from the perspective of reducing the energy consumption of the electrolytic zinc process, increasing the service life of the DSA anode and reducing the amount of anode mud generated, it is of great practical significance to improve the metal-based MnO2 coated electrode, increase its service life and reduce its preparation cost. Summary of the invention

[0010] The main purpose of the present invention is to provide a method for preparing a manganese oxide composite coating electrode, aiming to solve the problems of short life and low electrocatalytic activity of existing metal-based MnO2 electrodes.

[0011] In order to achieve the above object, the present invention adopts the following technical solution:

[0012] A manganese oxide composite coating electrode comprises a metal substrate, an anti-oxidation intermediate layer, a Yb doped MnO2 protective layer, and a Ce doped Mn2O3 catalytic layer; the metal substrate is selected from at least one of Al, Ti, Fe or their alloys, and the anti-oxidation intermediate layer is selected from at least one of TiN, TiB2, TiC, and WC.

[0013] A method for preparing a manganese oxide composite coating electrode, characterized in that: a Ce doped Mn2O3 catalyst layer comprises a metal substrate, an anti-oxidation intermediate layer, a Yb doped MnO2 protective layer prepared by an electrodeposition method, and a Cedoped Mn2O3 catalyst layer prepared by a thermal decomposition method; the electrode is prepared in the order of Ti substrate pretreatment → anti-oxidation intermediate layer → Yb doped MnO2 protective layer → Ce doped Mn2O3 catalyst layer.

[0014] After doping the MnO2 coating with ytterbium by electrodeposition, the bonding force between the coating and the substrate is much better than that of a single electrodeposited MnO2 layer. The coating becomes smoother and denser, with higher mechanical strength. It is difficult for the newly generated oxygen to penetrate it and reach the substrate surface during the electrolysis process, which effectively improves the service life of the electrode. However, after the addition of ytterbium, the catalytic activity of MnO2 decreases compared with before, so it is necessary to prepare a layer of Ce doped Mn2O3 on its surface to make up for the loss of electrocatalytic activity. The Ce part is doped into Mn2O3 in the form of CeO2, and the other part enters the Mn2O3 lattice, creating more oxygen vacancies to improve the oxygen evolution activity. This method also prepares a layer of anti-oxidation film with good chemical corrosion resistance and electrical conductivity between manganese dioxide and the metal matrix, which reduces the electron transfer resistance between the metal matrix and manganese dioxide and can prevent the oxidation of the metal matrix caused by excessive temperature during thermal decomposition.

[0015] The present invention has found through research that the life of the electrode prepared by the present invention is at least 6 times longer than that of the traditional Ti / MnO2 electrode, and its oxygen evolution potential in the electrolytic manganese solution is reduced by at least 50 mV.

[0016] In a preferred embodiment, the metal in the metal substrate is a pure metal or a hard alloy thereof, and the metal in the metal substrate is selected from at least one of Al, Ti and Fe.

[0017] Further preferably, the metal in the metal substrate is Ti.

[0018] Preferably, the anti-oxidation intermediate layer is selected from at least one of TiN, TiB2, TiC and WC.

[0019] Further preferably, the anti-oxidation intermediate layer is TiN.

[0020] When titanium metal is selected as the substrate and TiN is used as the anti-oxidation intermediate layer, the preparation process is simple, which greatly reduces the preparation cost and preparation time of the intermediate layer.

[0021] In a preferred embodiment, the TiN is prepared by gas nitriding, wherein the nitrogen source comprises at least one of nitrogen and ammonia, and the temperature is kept at a certain temperature for a period of time.

[0022] Further preferably, the nitriding nitrogen source is ammonia.

[0023] The inventors found that when a relatively active ammonia gas is used as a nitrogen source, it reacts more rapidly with the titanium substrate and the produced TiN film has less impurities.

[0024] Preferably, the ammonia nitriding insulation temperature is 700-1000°C, and the insulation time is 1-24 h.

[0025] Further preferably, Ti / TiN that meets the requirements of oxidation resistance and electrolyte corrosion resistance can be prepared by keeping the temperature at 850°C for 6 hours. When the temperature is lower than 800°C, the nitriding rate is slow, and when the temperature is higher than 900°C, the mechanical strength of the titanium substrate will be reduced.

[0026] Preferred solution: The method for preparing the Yb doped MnO2 layer by electrodeposition is to use Ti / TiN as the anode, metallic copper as the cathode, and MnSO4+Yb2(SO4)3+H2SO4 or Mn(CH3COO)2+Yb(CH3COO)3 as the electrolyte to perform constant current deposition at a certain temperature and current density. After deposition for 1 hour, take it out and put it into a 100°C oven to dry for 1 hour.

[0027] Further preference: when MnSO4+Yb2(SO4)3+H2SO4 is selected as the electrolyte, the MnSO4 concentration is 0.5-1.5 mol / L, preferably 1 mol / L, the Yb2(SO4)3 concentration is 5-15 mmol / L, preferably 8 mmol / L, the H2SO4 concentration is 0-1 mol / L, preferably 0.5 mol / L, the electrodeposition temperature is 70-95 °C, preferably 90 °C, and the current density is 10-30 mA / cm 2 , preferably 20 mA / cm 2

[0028] Further preference: When Mn(CH3COO)2+Yb(CH3COO)3 is selected as the electrolyte, the concentration of Mn(CH3COO)2 is 0.125~0.5 mol / L, preferably 0.3 mol / L, the concentration of Yb(CH3COO)3 is 10-20mmol / L, preferably 15 mmol / L, the electrodeposition temperature is 70~95°C, preferably 90°C, and the current density is 20-30 mA / cm 2 , preferably 25 mA / cm 2 .

[0029] Further preferably, the MnSO4+Yb2(SO4)3+H2SO4 system is selected as the electrolyte. The inventors have found that the Yb doped MnO2 layer prepared in the manganese acetate system has a relatively loose layered structure, more pores, and a relatively short lifespan. It is easily washed away by gas during the electrolysis process and dispersed into the solution.

[0030] In a preferred embodiment, the preparation method of the Ce doped Mn2O3 layer is to dissolve Ce salt in a Mn-containing solution to prepare a precursor solution, brush it evenly on the surface of Ti / TiN / Yb doped MnO2 with a brush, then place it flat in an oven for drying, then place it in a muffle furnace for thermal decomposition at a certain temperature, repeat the above steps several times, and finally place it in a muffle furnace for sintering.

[0031] Further preferred: the Mn-containing solution is 50% Mn(NO3)2 and is diluted to a certain concentration by one of anhydrous ethanol, isopropanol, n-butanol and distilled water.

[0032] Further preferred: the Ce salt is one of cerium chloride and cerium nitrate, preferably cerium nitrate.

[0033] Further preferably, the Ce salt concentration is 0.01-0.03 mol / L, preferably 0.02 mol / L

[0034] Further preferably, the drying temperature is 60-100°C, the thermal decomposition temperature is 150-350°C, the sintering temperature is 200-350°C, and the number of repetitions is 5-20 times, preferably 10 times.

[0035] Further optimization is as follows: the drying temperature is 90°C, the drying time is 10 min, the thermal decomposition temperature is 250°C, the thermal decomposition time is 10 min, the sintering temperature is 300°C, and the sintering time is 1 h.

[0036] The inventors have found that increasing the heat treatment temperature and heat treatment time will reduce the oxygen evolution activity of the electrode, but can increase the service life of the electrode. Excessively high heat treatment temperature and excessively long heat treatment time will gradually deepen the mud cracks on the electrode surface and may even lead to electrode inactivation. Low heat treatment temperature and short heat treatment time will make the prepared Cedoped Mn2O3 layer loose and easily brought into the precursor solution by the brush during the brushing process. However, after the Ce element is doped into the catalytic layer, the tolerance to the heat treatment temperature and heat treatment time is improved, and the electrocatalytic activity can be ensured not to decrease under the condition of increasing the heat treatment temperature.

[0037] In the present invention, although the bonding strength between the Yb doped MnO2 layer prepared by the electrodeposition method and the Ti / TiN substrate is greatly improved compared with the electrodeposited MnO2 layer, due to the difference in stress between the two, there are still phenomena such as instability and falling off. Therefore, it is necessary to etch the substrate to increase the roughness of the substrate, thereby increasing the contact surface between the Yb doped MnO2 layer and the metal substrate, enhancing the bonding strength between the Yb doped MnO2 layer prepared by the electrodeposition method and the Ti / TiN substrate, and the bonding strength can be optimized by controlling the oxalic acid concentration and the etching time.

[0038] In a preferred embodiment, the specific process of etching is: placing the polished titanium substrate in a trisodium solution for degreasing treatment, then cleaning the substrate surface with anhydrous ethanol, and then placing the substrate in a boiling oxalic acid solution for etching for 1 hour, wherein the oxalic acid solution is an aqueous solution of oxalic acid with a mass fraction of 10%, and the trisodium solution is an aqueous solution of sodium hydroxide, sodium phosphate, and sodium carbonate.

[0039] The inventors found that the etching time of the metal substrate in the boiling oxalic acid solution needs to be extended to 1.5 hours to achieve a good effect, which can improve the bonding strength of the composite anode to a certain extent.

[0040] Further preferably, when the mass ratio of each part in the trisodium solution is NaOH:Na3PO4:Na2CO3:H2O=2:2:1:40, a good oil removal effect can be achieved by immersing for 10 minutes.

[0041] The advantages and positive effects of the present invention are:

[0042] 1) When using traditional Ti / MnO2 electrodes for non-ferrous metallurgical electrodeposition, if the thermal decomposition method is used to prepare the Mn2O3 catalyst layer, there are many cracks on its surface, and the surface layer is porous and loose, which is easily eroded into the electrolyte by the airflow. In addition, during thermal decomposition, the high temperature easily causes the Ti substrate to oxidize, resulting in a high electrode potential. These are also the reasons why the Ti / MnO2 electrode has a short life. The MnO2 catalyst layer prepared by the electrodeposition method is dense and smooth, but its bonding ability with the substrate is very poor. It is very easy to fall off as a whole piece during the electrolysis process. In addition, the current density during the preparation process is very low, which makes the growth of the MnO2 layer very slow. Therefore, this is also the reason why the electrodeposited MnO2 layer is generally not used in electrode preparation. The inventors of the present invention have found that after adding ytterbium elements to the MnO2 layer, the bonding strength between the electrodeposited MnO2 layer and the substrate can be greatly improved, and the service life of the electrode can be greatly prolonged. However, its main disadvantage is that the anode potential will rise by about 300 mV. The use of Ce doped Mn2O3 as the catalytic layer can not only reduce the anode potential of the electrode but also further improve the service life of the electrode. In addition, the addition of Ce elements can reduce the generation of surface cracks, increase the durability of the electrode, and improve the catalytic activity of the electrode, so that the service life of the electrode is extended by more than 6 times that of the Ti / Mn2O3 electrode prepared by thermal decomposition.

[0043] 2) For the first time, the ytterbium doping method was used to improve the durability of electrodeposited MnO2, and the method of combining it with the Ce-doped Mn2O3 catalyst layer was used to increase the service life of the electrode, which can ensure its electrocatalytic activity and inhibit the Mn 2+ Depletion can also improve the durability of the electrode.

[0044] 3) Ytterbium-doped MnO2 is used as a protective layer, and Ce-doped Mn2O3 is used as a catalytic layer. Although its preparation process is relatively complicated compared to precious metal oxide electrodes such as IrO2 and RuO2, its preparation method is relatively simple and has a good electrode service life. Moreover, its price is relatively low and it has great prospects for industrial application.

[0045] 4) The electrode also has good reusability. As the polarization process proceeds, the Cedoped Mn2O3 catalytic layer of the electrode is easily destroyed by airflow flushing, but the Yb doped MnO2 layer will not fall off or break during the polarization process. Therefore, when the anode potential is found to rise to a certain value, the electrode can be taken out, dried, and then the Mn2O3 catalytic layer can be re-prepared on it, which greatly improves the reusability of the electrode. Each electrode can be reused for at least three rounds, which can prevent electrode passivation caused by rupture of the catalytic layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The anode potential change curve of the accelerated life test of Ti / Yb doped MnO2 / Ce doped Mn2O3 electrode and Ti / Mn2O3 electrode is shown in the figure. The preparation conditions of the composite electrode are: the optimal preparation process is used for electrodeposition of Yb doped MnO2, and the deposition is 1.5h. The thermal decomposition Ce doped Mn2O3 layer is brushed with 10 layers using the optimal preparation process, and the Ti / Mn2O3 electrode is brushed with 30 layers. The accelerated life test conditions are: H2SO4 2 mol / L, current density 1A / cm 2 , the counter electrode is a platinum electrode, the reference electrode is a saturated calomel electrode, and the anode potential rises to 10 V, indicating electrode failure.

[0047] Specific implementation cases:

[0048] The following are typical examples of the present invention, but it should be understood that the present invention is not limited to these examples.

[0049] Embodiment 1:

[0050] The method of the present invention is used to prepare a Ti / TiN / electrodeposited Yb doped MnO2 layer / thermally decomposed Ce doped Mn2O3 layer electrode, which is used as an anode in the electrolytic zinc process.

[0051] The metal titanium substrate used was in plate shape. After being polished smooth, the surface was degreased with a trisodium solution, then etched in a 10% oxalic acid solution for 1.5 h. Then the TiN layer was prepared using ammonia as the nitrogen source at 850 °C for 6 h, and its thickness was about 3 μm.

[0052] Yb doped MnO2 selection: MnSO4+Yb2(SO4)3+H2SO4 as electrolyte, MnSO4 concentration is 1 mol / L, Yb2(SO4)3 concentration is 8 mmol / L, H2SO4 concentration is 0.5 mol / L, electrodeposition temperature is 90 ℃, current density is 20 mA / cm 2 The Ce doped Mn2O3 layer was prepared by using a mixture of isopropanol and manganese nitrate in a volume ratio of 10:6 as solvent and cerium nitrate as solute. 3+ The concentration of the precursor solution is 0.02 mol / L, the drying temperature is 90 ℃, the drying time is 10 min, the thermal decomposition temperature is 250 ℃, the thermal decomposition time is 10 min, and after repeated brushing 10 times, it is sintered at 300 ℃ for 1 h.

[0053] The prepared composite anode was used in a simulated zinc electrolysis experiment, and the cathode was a flat metal aluminum.

[0054] The electrolyte composition is ZnSO4 (Zn2+ 55g / L)、MnSO4 (Mn 2+ 3g / L), H2SO4 (160g / L), at 40°C with 500 A / m 2 Electrodeposition was carried out for 24 h at an anodic current density of 1.34°. Compared with the existing Pb-Ag alloy anode, the anode potential dropped by 200 mV, and no anode mud was generated at the bottom of the anode chamber.

[0055] The prepared composite anode was subjected to an accelerated life test in a simulated zinc electrolytic anode solution, and the cathode was a platinum electrode.

[0056] The electrolyte composition is 2 mol / L H2SO4 solution, and the current density is 1 A / cm 2 , the electrode distance was 5 cm. When the anode potential exceeded 10 V during electrolysis, the electrode was considered to be failed and the experiment was stopped immediately. It was found that the experimental life of the electrode was 43h.

[0057] The prepared anode was subjected to XPS test, and Mn 2p , Mn 3s , O 1s The orbital peak fitting is performed by comparing the Mn 3 + / Mn 4+ , average oxidation state (AOS) and surface oxygen / lattice oxygen (O ads / O latt ) and other parameters to reflect the content of oxygen vacancies in the catalytic layer, and further compare their theoretical oxygen evolution activities. 3+ / Mn 4+ The higher the ratio, the higher the oxygen vacancy content, the higher the electrocatalytic activity; the smaller the value of the average oxidation state (AOS), the higher the electrocatalytic activity. ads / O latt ) ratio, the larger the electrocatalytic activity. 3+ / Mn 4+ =0.20, AOS=2.93, O ads / O latt =0.47.

[0058] Comparative Example 1:

[0059] The treatment of the titanium substrate and the preparation of the TiN layer are the same as those in Example 1. After the substrate is treated, the number of Ti / Mn2O3 electrode brush coatings is 30 layers directly prepared by thermal decomposition. The conditions used in the electrolytic zinc and accelerated life test of the electrode are exactly the same as those in Example 1. The experiment shows that during the electrolytic zinc process, its anode potential drops by 190 mV compared with the lead anode, and no anode mud is generated at the bottom of the anode chamber, but its performance in the accelerated life test is very poor, only 7 h.

[0060] Comparative Example 2:

[0061] The treatment of the titanium substrate and the preparation of the TiN layer are the same as those in Example 1. After the substrate is treated, the Ti / MnO2 electrode is directly prepared by electrodeposition, and the plating time is 2 h. The conditions used in the electrolytic zinc and accelerated life test of the electrode are exactly the same as those in Example 1. The experiment shows that during the electrolytic zinc process, its anode potential drops 160 mV compared with the lead anode, but the electrolytic process cannot complete an electrolytic cycle. Although no anode mud is generated at the bottom of the anode chamber, its service life is extremely low. Calculation of XPS fitting data shows that Mn 3+ / Mn 4+ =0.21, AOS=3.25, O ads / O latt =0.37.

[0062] Comparative Example 3:

[0063] The treatment method of the Ti / TiN electrode is the same as that of Example 1, and then a Ti / TiN / Yb doped MnO2 electrode is prepared by electroplating on the Ti / TiN surface. The preparation conditions of the electroplated Yb doped MnO2 are exactly the same as those of Comparative Example 1, and the plating time is extended to 2 hours. The conditions used in the electrolytic zinc and accelerated life test of the electrode are exactly the same as those of Example 1. The experiment shows that during the electrolytic manganese process, its anode potential is about 50mV higher than that of the lead anode, and no anode mud is generated at the bottom of the anode chamber, but its accelerated life test shows that the life has been extended to 57 hours. Calculation of XPS fitting data shows that Mn 3+ / Mn 4+ =0.09, AOS=3.68, O ads / O latt =0.25.

[0064] Comparative Example 4:

[0065] The treatment method of Ti / TiN electrode is the same as that of Example 1. Then, Ti / TiN / Ce doped Mn2O3 electrode is prepared by thermal decomposition on the Ti / TiN surface. The preparation conditions are exactly the same as those of Comparative Example 1, and the number of brushing is 30 layers. The conditions used in the electrolytic zinc and accelerated life test of the electrode are exactly the same as those of Example 1. The experiment shows that during the electrolytic zinc process, its anode potential drops by 300 mV compared with the lead anode, and a small amount of anode mud is generated at the bottom of the anode chamber. It should be that during the electrolysis process, the thermal decomposition layer is washed off by the gas and falls to the bottom of the electrolytic cell. Its life in the accelerated life test is 17 h. Calculation of XPS fitting data shows that Mn 3+ / Mn 4+ =0.24, AOS=2.65, Oads / O latt =0.51.

[0066] Comparative Example 5:

[0067] The order of Yb doped MnO2 and Ce doped Mn2O3 in Example 1 was reversed, but the preparation method was exactly the same, and the electrolytic zinc and accelerated life test process were exactly the same as in Example 1. The experiment showed that the electrode potential was 110 mV higher than that of the lead anode during the electrolytic zinc process, and its accelerated life was reduced to 35 h compared with that in Example 1. The XPS fitting data was calculated to obtain Mn 3 + / Mn 4+ =0.11, AOS=3.56, O ads / O latt =0.21.

Claims

1. A manganese oxide composite coating electrode, characterized in that: It includes a metal substrate, an anti-oxidation intermediate layer, a Yb-doped MnO2 protective layer, and a Ce-doped Mn2O3 catalytic layer; the metal substrate is selected from at least one of Al, Ti, Fe or their alloys, and the anti-oxidation intermediate layer is selected from at least one of TiN, TiB2, TiC, and WC; the manganese oxide composite coating electrode is prepared in the order of pretreating the metal substrate, preparing the anti-oxidation intermediate layer, preparing the Yb-doped MnO2 layer, and preparing the Ce-doped Mn2O3 layer.

2. The method for preparing a manganese oxide composite coating electrode according to claim 1, characterized in that: The preparation method of the anti-oxidation intermediate layer is a method that does not cause oxidation of the metal or alloy substrate. The preparation method of the anti-oxidation intermediate layer is one of in-situ synthesis, plasma spraying, and magnetron sputtering. The thickness of the anti-oxidation intermediate layer is 5 to 100 μm.

3. The method for preparing a manganese oxide composite coating electrode according to claim 2, characterized in that: The anti-oxidation intermediate layer is TiN, the preparation method of TiN is gas nitriding method, the nitriding nitrogen source used in the gas nitriding method is ammonia, the insulation temperature of ammonia nitriding is 700-1000° C., and the insulation time is 1-24 hours.

4. The method for preparing a manganese oxide composite coating electrode according to claim 1, characterized in that: The preparation method of Ce-doped Mn2O3 is to dissolve Ce salt in a Mn-containing solution to prepare a precursor solution, then use a brush to evenly brush the precursor solution on the surface of the electrode, then put it in an oven to dry the organic solvent, then put it in a muffle furnace for thermal decomposition, repeat the above steps several times, and finally put it in a muffle furnace for sintering.

5. The method for preparing a manganese oxide composite coating electrode according to claim 4, characterized in that: The Mn-containing solution is a solution of 50% Mn(NO3)2 diluted by a diluent, wherein the diluent is one of anhydrous ethanol, isopropanol, n-butanol, and distilled water; the Ce salt is one of cerium nitrate and cerium chloride, and the concentration of the Ce salt is 0.01-0.03 mol / L.

6. The method for preparing a manganese oxide composite coating electrode according to claim 4, characterized in that: The drying temperature is 60-100° C., the thermal decomposition temperature is 150-350° C., the sintering temperature is 200-350° C., and the number of repetitions is 5-20 times.

7. The method for preparing a manganese oxide composite coating electrode according to claim 1, characterized in that: The preparation method of the Yb-doped MnO2 layer is to use the metal substrate / anti-oxidation intermediate layer as the anode, metal copper as the cathode, and MnSO4+Yb2(SO4)3+ H2SO4 or Mn(CH3COO)2+ Yb(CH3COO)3 as the electrolyte for constant current deposition, and then take it out after deposition and put it into an oven for drying.

8. The method for preparing a manganese oxide composite coating electrode according to claim 7, characterized in that: When MnSO4 + Yb2(SO4)3 + H2SO4 is selected as the electrolyte, the concentration of MnSO4 is 0.5-1.5 mol / L, the concentration of Yb2(SO4)3 is 5-15 mmol / L, the concentration of H2SO4 is 0-1 mol / L, the temperature of constant current deposition is 70-95℃, and the current density is 10-30mA / cm 2 ; When Mn(CH3COO)2 +Yb(CH3COO)3 is selected as the electrolyte, the concentration of Mn(CH3COO)2 is 0.125-0.5 mol / L, the concentration of Yb(CH3COO)3 is 10-20 mmol / L, the temperature of constant current deposition is 70-95°C, and the current density is 20-30 mA / cm 2 .

9. The method for preparing a manganese oxide composite coating electrode according to claim 1, characterized in that: The method for pretreating the metal substrate is to first deoil the wire substrate in a trisodium solution, then polish it with sandpaper to remove the surface oxide layer, then immerse the polished metal substrate in the trisodium solution for further deoiling, and then place the metal substrate in an oxalic acid solution and etch it for 1.5 hours under boiling; wherein the trisodium solution is a mixed solution of sodium carbonate, sodium phosphate and sodium hydroxide; and the mass fraction of oxalic acid in the oxalic acid solution is 10%.

Citation Information

Patent Citations

  • Nanocrystalline manganese bioxide coated anode and method for making same

    CN101225526A

  • Titanium-based manganese-iridium composite oxide coating anode and preparation method thereof

    CN101230467A